EGFR-PI3K-AKT-mTOR signaling in head and neck squamous cell carcinomas: attractive targets for molecular-oriented therapy - Freudlsperger, Christian; Burnett, Jeffrey R; Friedman, Jay A; Kannabiran, Vishnu R; Chen, Zhong; Van Waes, Carter (Expert opinion on therapeutic targets, 2011)
Importance of the field: Recent advances in the understanding of the oncogenesis of head and neck squamous cell carcinomas (HNSCC) have revealed multiple dysregulated signaling pathways. One frequently altered axis is the EGFR-PI3K-Akt-mTOR pathway. This pathway plays a central role in numerous cellular processes including metabolism, cell growth, apoptosis, survival and differentiation, which ultimately contributes to HNSCC progression. Areas covered in this review: Books, journals, databases and websites have been searched to provide a current review on the subject. What the reader will gain: This article reviews the current understanding of EGFR-PI3K-Akt-mTOR signaling in HNSCC, including the impact of both genetic and epigenetic alterations. This review further highlights the potential of targeting this signaling cascade as a promising therapeutic approach in the treatment of HNSCC. Take home message: Genetic alterations of several nodes within this pathway, including both genetic and epigenetic changes, leading to either oncogene activation or inactivation of tumor suppressors have frequently been implicated in HNSCC. Consequently, drugs that target the central nodes of this pathway have become attractive for molecular oriented cancer therapies. Numerous preclinical and clinical studies are being performed in HNSCC; however, more studies are still needed to better understand the biology of this pathway.
Autorenmanuskript, verfügbar in PMC 2012 Juli 18
Online veröffentlicht: 26 Nov 2010
Gesehen am 08.03.2023